Kajian Proses Pencatatan Utang Usaha Pada Divisi Account Payable Di PT Gobel Dharma Sarana Karya - Abella Saniyyah; Dwiyatmoko Puji Widodo; Yuni Siti Nuraeni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract This study aims to analyze the accounts payable recording procedures in the Accounts Payable (AP) Division at PT Gobel Dharma Sarana Karya. Effective management of accounts payable is crucial for the financial stability of a company, and accurate recording ensures that the company’s liabilities are well-managed. This research employs a qualitative method, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that the accounts payable recording procedures at PT Gobel Dharma Sarana Karya involve several key documents, including Purchase Orders (PO), Receiving Reports (RR), Invoices, and Payment Bank Vouchers (PBV). Although the company has implemented an integrated information system to support this process, challenges such as delays in document submission and data entry errors still affect the efficiency of accounts payable recording. The study concludes that PT Gobel Dharma Sarana Karya should enhance the information technology in use and improve coordination among related departments. Recommendations include the implementation of automation technology, regular staff training, and improved inter-departmental coordination to ensure more efficient and accurate accounts payable recording